Phosphorus micro-dosing as an entry point to sustainable intensification of rice systems in sub-Saharan Africa - Vandamme, Elke; Ahouanton, K.; Mwakasege, L.; Mujuni, S.; Mujawamariya, Gaudiose; Kamanda, J.; Senthilkumar, Kalimuthu; Saito, Kazuki (Elsevier, 2018)
Phosphorus (P) deficiency is a major biophysical limitation to rice grain yields in sub-Saharan Africa, and low-cost P management strategies are needed by smallholder farmers to reverse soil fertility decline. On-station field and pot experiments were combined with on-farm testing to evaluate the effect of P micro-dose placement in dry-seeded, dibbled rice on emergence, early vigour and grain yield. Placing a micro-dose of 3–6 kg P ha−1 in the planting hole consistently increased early vigour and grain yield of both a P-efficient and less P-efficient rice genotype. An agronomic efficiency of P fertilizer (AEP) of 356–817 kg grains kg−1 P was achieved with a micro-dose of 3 kg P ha−1. A negative effect on emergence by placing a P micro-dose in the planting hole observed in one experiment was compensated by a higher grain weight per hill. In other experiments, no negative effect on plant emergence under both well-watered and water-stressed conditions and with different P sources was observed even when fertilizers were mixed with seeds. A micro-dose of 20–30 kg of DAP ha−1 placed in the planting hole resulted in an average net increase in profit of $91 to $136 ha−1 and benefit:cost ratio of 3–12 in on-farm experiments. Farmers' appreciation of the technology was positive but lack of credit, availability of appropriate fertilizers in local agrodealers and increased labour requirements were identified as potential constraints for adoption. P micro-dose placement in the planting hole can be used as an entry point towards sustainable intensification in dry-seeded, dibbled rice systems in SSA, provided it is accompanied by institutional support and mechanization options to increase its adoption potential.